Towards Democracy in the Hungarian Science of Education and School-System - Kotschy, Beáta; Golnhofer, Erzsébet (European Journal of Mental Health, 2008)
Towards Democracy in the Hungarian Science of Education and School-System: Through the developments of the education sciences and the education system, this study presents two major historical changes of the post World War II period in Hungary – hopes regarding democratic reconstruction and their quelling after 1945, and the aspirations of the years of political change in the 1990s following the collapse of the communist dictatorship to restore and develop a pluralised, democratic society and education system. Through the changes to the conditions surrounding education sciences, the first part of the study displays the consequences of the political dictatorship taking over power, regarding the development of scientific institutions, professional journals, the professional sphere and the lives of individual researchers. It introduces the illusions of the post-war years, the hope of constructing a democratic Hungarian society, the revival of various schools of pedagogy (human sciences, cultural pedagogy, nation-education, popular movements and reform pedagogy trends), and the realisation of pluralism in professional literature. This is followed by the ‘results’ of the communist takeover – establishing political control over scientific institutions, steeping professional manifestations in politics, persecuting civil pedagogies, and sidelining their representatives, regardless of whether their views were opposed or closely related to socialist ideals, and whether they chose political opposition or varying degrees of conformism in their individual behaviour. Pointing to the political, economic and social reasons for the collapse of the dictatorship, the second part of the study lays out the background of the different views concerning the construction of a democratic society – the concepts building on Hungarian precedents and stressing continuity, the efforts calling for copying the examples of western democracies, and finally the proposals drawing on a trusted and particular Central and Eastern European way. The results of the three political and social approaches are three different school systems, education governance systems that are based on different sets of values. As a result of political preferences, these differences on the professional level turned into ammunition in the fight between parties, and consequently raise serious barriers in the way of carrying out democratic change. The final part of the study summarises the changes required that are the basic conditions for decentralising and democratising the education system – accepting pluralism in pedagogy, a new approach to the role of the school and teacher, to understanding freedom and responsibility in pedagogy, to schools open towards society and the parents, and to the necessity of new procedures in the training of teachers.